Pharmacy Students’ Retention of Knowledge of Drug-Drug Interactions - Gilligan, Adrienne M. (American Journal of Pharmaceutical Education, 2011)
Objectives. To evaluate pharmacy students' drug-drug interaction (DDI) knowledge retention over 1 year and to determine whether presenting DDI vignettes increased knowledge retention. Methods. A knowledge assessment tool was distributed to fourth-year pharmacy students before and after completing a DDI educational session. The questionnaire was re-administered after 1 year to assess knowledge retention. During the intervening year, students had the option of presenting DDI case vignettes to preceptors and other health professionals as part of their advanced pharmacy practice experiences (APPEs). Results. Thirty-four of 78 pharmacy students completed both the post-intervention and 1-year follow-up assessments. Students’ knowledge of 4 DDI pairs improved, knowledge of 3 DDI pairs did not change, and knowledge of the remainder of DDI pairs decreased. Average scores of the 18 students who completed all tests and presented at least 1 vignette during their APPEs were higher on the 1-year follow-up assessment than students who did not, suggesting greater DDI knowledge retention (p = 0.04). Conclusion. Although pharmacy students’ overall DDI knowledge decreased in the year following an educational session, those who presented vignettes to health professionals retained more DDI knowledge, particularly on those DDIs for which they gave presentations. Other methods to enhance pharmacy students’ retention of DDI knowledge of clinically important DDIs are needed.